Multiplexed assays to determine the selectivity of anti-GPCR antibodies - Dahl, Leo; Kotliar, Ilana B.; Bendes, Annika; Dodig-Crnkovic, Tea; Fromm, Samuel; Elofsson, Arne; Uhlén, Mathias; Sakmar, Thomas P.; Schwenk, Jochen (Royal Institute of Technology, 2023)
Description of study and method

This dataset contains measurement values from a multiplexed screen of antibodies (Abs) to determine their selective recognition of G protein-coupled receptors (GPCRs).

Therapeutic antibodies are being developed to modulate GPCR function. However, validating the selectivity of anti-GPCR Abs is challenging due to sequence similarities of individual receptors within GPCR subfamilies. Here we present data from multiplexed immunoassay to test >400 anti-GPCR Abs from the Human Protein Atlas targeting a customized library of 215 expressed and solubilized GPCRs representing all GPCR subfamilies.

The GPCRs were conjugated with 1D4 and FLAG epitope tags (common protein tags for Ab binding), were overexpressed in Expi293F cells and solubilized for the assay. The Abs were tested using the suspension bead array (SBA) technology from Luminex. The technology employs color-coded beads with Abs that bind the target (for capture) and fluorescently labelled Abs that bind the 1D4 epitope tag (for detection). The resulting output data are the median fluorescence intensity (MFI) values for each sample and Ab. MFI represents a relative measurement that allows for comparison within Abs but not between. The dataset also contains Z-scores and robust Z-scores for visualization and to provide a similar scale for all Abs. For Ab validation, Abs targeting GPCRs were used for capture. To verify that GPCRs were expressed at all, Abs targeting the FLAG tag were used for capture.

Each anti-GPCR Ab was evaluated against its target GPCR and phenotypically closely related GPCRs by using a population density-based threshold to map the on-target and off-target binding of the antibody.



The files contain the following data and information

- abval_dat.csv: Sample information and Luminex measurements (MFI, Z-scores and robust Z-scores) for samples used in the antibody validation screen (GPCR capture, 1D4 detection).

- expr_dat.csv: Sample information and Luminex measurements for lysates used to evaluate GPCR expression (FLAG capture, 1D4 detection).

- prot.csv: Information about antibodies used in the study.

- ReadMe: Details about the files and description of columns
Keywords: Receptors and membrane biology; Analytical biochemistry; Proteomics and intermolecular interactions (excl. medical proteomics); Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi; Biological Sciences; Biologi